Predicting the Importance of Hospital Chaplain Care in a Trauma Population - Berg, Gina M; Crowe, Robin E; Borchert, Shannon; Siebert, Jane; Lee, Felecia (Kansas Journal of Medicine, 2012)
Background. The purpose of this exploratory study was to determine if the importance of chaplain care is associated with and could be predicted by patient or injury characteristics. Methods. A telephone survey of recently discharged trauma patients was conducted. Logistic regression analyses were conducted to determine what factors are associated with the importance of chaplain care and satisfaction with chaplain care. Results. Self-reported religious affiliation was associated with the importance of chaplain care and importance of chaplain care was associated with satisfaction with chaplain care. Conclusions. The value of chaplain care cannot be measured by patient characteristics, therefore, chaplain care should be offered to all patients and families.